(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The Torfaen Sports Development Team (Wales, United Kingdom) established the #ifyougoigo programme, which seeks to leverage key facilitators, such as social support and companionship, to increase physical activity (PA) and physical literacy among women. The programme includes group-based exercise sessions, one-to-one personal training, educational workshops, and opportunities to try new sports. This research assessed the broad impact of the intervention and specifcally explored the relationship between physical literacy, companionship, and self-efcacy within the Self-Determination Theory framework. Methods: Women accepted onto the 10-week programme (n = 38, 41.5 ± 10.1 years) had their body mass, arm, thigh, and stomach circumferences, six-minute walking distance (sessional rate of perceived exertion recorded), National Health Service (NHS) resource usage, and device-based PA measured at four time-points. Furthermore, quality of life, perceived capability and wellbeing were measured using the EQ-5D and ICE-CAP surveys. Linear mixed regressions were used to assess the change from the pre- to post-intervention. Finally, participants also completed follow-up interviews (one-month post-programme) and focus groups (six months post-programme), which were analysed thematically. Results: Quantitative measures did not indicate signifcant change, however promising trends in key variables were identifed. Downward trends in body mass (p = 0.091), body mass index (p = 0.091), and self-perceived anxiety and depression (p = 0.654); together with an increased sense of independence (p = 0.654), sense of achievement and progress (p = 0.654), and enjoyment and pleasure (p = 0.653) all indicate a positive programme impact trajectory at a larger scale. Qualitative fndings highlighted that the group exercise dynamic served as a vehicle for self-reﬂection, fostering emotional and social safety alongside enjoyment. Conclusion: The #ifyougoigo programme positively impacted women’s mental and physical health through group-based PA engagement. These fndings provide practical insights for the design and implementation of future community-based interventions and can inform funding strategies to scale the programme to reach broader populations. Support/Funding Source: Torfaen County Borough Council